GW5‐Like, a homolog of GW5, negatively regulates grain width, weight and salt resistance in rice. Issue 11 (1st February 2019) - Tian, Peng; Liu, Jiafan; Mou, Changling; Shi, Cuilan; Zhang, Huan; Zhao, Zhichao; Lin, Qibing; Wang, Jie; Wang, Jiulin; Zhang, Xin; Guo, Xiuping; Cheng, Zhijun; et al.
Abstract: Grain size is an important determinant of yield potential in crops. We previously demonstrated that natural mutations in the regulatory sequences of qSW5/GW5 confer grain width diversity in rice. However, the biological function of a GW5 homolog, named GW5‐Like (GW5L), remains unknown. In this study, we report on GW5L knockout mutants in Kitaake, a japonica cultivar (cv.) considered to have a weak gw5 variant allele that confers shorter and wider grains. GW5L is evenly expressed in various tissues, and its protein product is localized to the plasma membrane. Biochemical assays verified that GW5L functions in a similar fashion to GW5. It positively regulates brassinosteroid (BR) signaling through repression of the phosphorylation activity of GSK2. Genetic data show that GW5L overexpression in either Kitaake or a GW5 knockout line, Kasa orf3 ( indica cv. Kasalath background), causes more slender, longer grains relative to the wild‐type. We also show that GW5L could confer salt stress resistance through an association with calmodulin protein OsCaM1‐1. These findings identify GW5L as a negative regulator of both grain size and salt stress tolerance, and provide a potential target for breeders to improve grain yield and salt stress resistance in rice. Abstract : We identified a new rice grain size‐related gene, GW5‐Like, and examined its biological function. We found this gene negatively regulates both grain size and salt stress tolerance, and it could serve as a potential target for genome editing to improve grain yield and salt tolerance in rice.